Gene expression profiling in Rosa roxburghii fruit and overexpressing RrGGP2 in tobacco and tomato indicates the key control point of AsA biosynthesis - Yan, Yali; Liu, Yiyi; Lu, Min; Lu, Chen; Ludlow, Richard A.; Yang, Man; Huang, Wei; Liu, Zeyang; An, HuaMing (Frontiers in Plant Science, 2023)
Rosa roxburghii Tratt. is an important commercial horticultural crop endemic to China, which is recognized for its extremely high content of L-ascorbic acid (AsA). To understand the mechanisms underlying AsA overproduction in fruit of R. roxburghii, content levels, accumulation rate, and the expression of genes putatively in the biosynthesis of AsA during fruit development have been characterized. The content of AsA increased with fruit weight during development, and AsA accumulation rate was found to be highest between 60 and 90 days after anthesis (DAA), with approximately 60% of the total amount being accumulated during this period. In vitro incubating analysis of 70DAA fruit flesh tissues confirmed that AsA was synthesized mainly via the L-galactose pathway although L-Gulono-1, 4-lactone was also an effective precursor elevating AsA biosynthesis. Furthermore, in transcript level, AsA content was significantly associated with GDP-L-galactose phosphorylase (RrGGP2) gene expression. Virus-induced RrGGP2 silencing reduced the AsA content in R. roxburghii fruit by 28.9%. Overexpressing RrGGP2 increased AsA content by 8-12-fold in tobacco leaves and 2.33-3.11-fold in tomato fruit, respectively, and it showed enhanced resistance to oxidative stress caused by paraquat in transformed tobacco. These results further justified the importance of RrGGP2 as a major control step to AsA biosynthesis in R. roxburghii fruit.